Koncepcja rachunku zysków i strat w projekcie MSSF dla małych i średnich przedsiębiorstw a funkcja informacyjna rachunku kosztów - Zuchewicz, Joanna (The concept of profit and loss account in the project of IAS for small and medium enterprises vs. informative function of costs account, 2008)
In February 2007 International Standards Accounting Board presented for discussion the project of IAS referring to financial reporting of small and medium enterprises (SME). The project defines SME as a unit "not keeping public financial reporting", but issuing reports for external users. The project presents an IAS compendium for small and medium entities. It does not include ready samples of financial reports, but only offers a minimal set of data which have to be revealed. The objective of the article was to study the usefulness of information included in the profit and loss account project, offered for SME in conducting costs analysis and an interpretation referring to overall functioning of a small and medium entity. From the point of view of informative function implementation - internal costs account, dealing in providing information related to costs in order to manage them and other areas of an enterprise activity at both strategic, tactic, and operational level, the data presented in the suggested profit and loss account are insufficient and require many supplements in additional subsystems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 479-486